2018
DOI: 10.1155/2018/6298739
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dyslipidemia among Jordanians

Abstract: Background Dyslipidemia is one of the major modifiable risk factors for the development of cardiovascular disease and type two diabetes mellitus. Knowing the current prevalence of dyslipidemia is an important step for increasing awareness of the problem and for proper planning of health programs for prevention of its negative clinical effects. Methods A national population based household sample was selected from north, middle, and south regions of Jordan in 2017. A total sample of 4,056 aged between 18 and 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
50
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 14 publications
15
50
8
Order By: Relevance
“…In this study, CVDs RFs prevalence results demonstrated similar results of a study performed in Africa and the Middle East (AfME) region [ 20 ]. This study revealed prevalence of overall dyslipidemias within the Jordanian population reflective of other Jordanian reports [ 21 ]. Fasting lipid profile is not routinely included within the Jordanian screening program unlike BP and BS despite the international recommendation of consistent screening [ 22 ].…”
Section: Discussionsupporting
confidence: 77%
“…In this study, CVDs RFs prevalence results demonstrated similar results of a study performed in Africa and the Middle East (AfME) region [ 20 ]. This study revealed prevalence of overall dyslipidemias within the Jordanian population reflective of other Jordanian reports [ 21 ]. Fasting lipid profile is not routinely included within the Jordanian screening program unlike BP and BS despite the international recommendation of consistent screening [ 22 ].…”
Section: Discussionsupporting
confidence: 77%
“…That study also documented an increased rate of obesity in the 10 years preceding the survey [10]. This increase in obesity coincided with increased rates of diabetes, hypertension, and dyslipidemia in Jordan [11][12][13]. Ten years later, a representative survey using a larger sample size was conducted in the same country.…”
Section: Discussionmentioning
confidence: 76%
“…A prevalence of 87% is above all these conditions. Some studies for hypercholesterolemia in general population found levels between 20% and 60%, depending on alimentary habits and direct corelated with obesity 12,13 .…”
Section: Methodsmentioning
confidence: 99%